C Cicil Emas dan Stabilitas Keuangan PNS: Studi Kasus Nasabah KCP Probolinggo Kraksaan: Implementasi Produk Cicil Emas di BSI KCP Probolinggo Kraksaan - Ainul Muluk, Moh Hasan (Maliki Interdisciplinary Journal, 2026)
The Gold Installment product is an innovation from Pegadaian that allows customers to buy gold in installments, with the main advantages being a safe investment and potential profits from rising gold prices. Especially for Civil Servant (PNS) customers at the Probolinggo Kraksaan Sub-Branch Office (KCP), this product offers benefits such as easy access without additional collateral requirements, flexible installments adjusted to civil servant salaries, as well as stable asset value protection amidst economic fluctuations. Other advantages include a fast administration process, competitive interest, and the option to redeem gold at any time without heavy penalties, making it suitable for long-term financial planning. The study highlights how this product is improving the financial wellbeing of civil servants in the region, with data showing a 30% increase in customer interest in the last six months. In conclusion, Gold Installments are not only an investment tool, but also a tool of economic empowerment for civil servant groups.